Absence of Neck Scars With Total Endoscopic Submandibular Sialadenectomy Using a Chest Wall Approach: A New Technique. (February 2018) - Elzahaby, Islam A.; Khater, Ashraf; Abdallah, Ahmed; Refky, Basel; Abd Elaziz, Mahmoud; Shetiwy, Mosab; Zaid, Amir M.
Introduction . This study aims to demonstrate the safety, surgical feasibility, and esthetic features of total endoscopic submandibular sialadenectomy through a chest wall approach without the creation of any neck incisions. Methods . Four patients with benign submandibular gland lesions underwent a total endoscopic submandibular sialadenectomy through a chest wall approach using 3 ports (one 10-mm port for the camera and two 5-mm ports for the working instruments). Results . The operative time ranged from 140 to 170 minutes. Conversion to the open technique was only necessary in one case with good visualization of the facial vein and artery, marginal mandibular and lingual nerve. No significant perioperative complications were encountered. All patients were discharged on the third postoperative day, and they were satisfied with the cosmetic outcome. Conclusion . Total endoscopic submandibular sialadenectomy through a chest wall approach is technically feasible and safe with satisfactory cosmetic results. It may be a valid alternative to conventional surgery when performed in select patients. The absence of neck scars and the ability to avoid potential nerve injuries are the most obvious advantages of this innovative technique.